The South China Sea arbitration a Chinese perspective - Talmon, Stefan 1965-; Jia, Bing-Bing 1966- (Hart Publishing, 2014)
The book aims to offer a Chinese perspective on some of the issues raised in the arbitral proceedings of the South China Sea dispute between the Republic of the Philippines and the Peoples Republic of China.